Simultaneously improved dielectric and mechanical properties of silicone elastomer by designing a dual crosslinking network. Issue 5 (10th January 2019) - Sun, Haibin; Liu, Xueying; Yu, Bing; Feng, Zhanbin; Ning, Nanying; Hu, Guo-Hua; Tian, Ming; Zhang, Liqun
Abstract : A homogenous silicone dielectric elastomer with simultaneously improved dielectric and mechanical properties is synthesized by designing a dual crosslinking network. Abstract : The application of silicone rubber (SiR) dielectric elastomer (DE) as an actuator is limited by its low properties in terms of dielectric constant, mechanical strength and actuated strain in a low electric field. This work aimed at simultaneously improving the dielectric and mechanical properties of SiR by designing a dual-crosslinking network (DN) of SiR, denoted as SiR-DN. First, carboxyl modified PMVS (PMVS-COOH) was synthesized by using a photochemical thiol–ene click reaction. Then PMVS-COOH was blended with a commercial silanol terminated polydimethylsiloxane (PDMS-OH) followed by the crosslinking of PDMS-OH using an amino (NH2 ) bearing crosslinking agent to form a PDMS-NH2 crosslinked network, forming a PMVS-COOH and PDMS-NH2 dual-crosslinking network. The as prepared DN structure includes the chemical crosslinked PDMS-NH2 network and the network formed by hydrogen bonds between PMVS-COOH and PDMS-NH2 . The PMVS-COOH can serve as a polar component to enhance the dielectric constant and the hydrogen bonds can serve as sacrificial bonds to strengthen SiR. Compared with reference SiR, the tensile strength, tensile toughness, dielectric constant and actuated strain at low electrical field (15 kV mm −1 ) of SiR-DN 1.5/1 (with the PMVS-COOH/PDMS-OH mass ratio of 1.5/1) were all largely improved. The reinforcing effect of SiR-DN is comparable with the most commonly used reinforcing methods of room temperature vulcanizing SiR by adding nanofillers. Meanwhile, the actuated strain at 15 kV mm −1 of SiR-DN 1.5/1 is much higher than that reported in most previous studies.